Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.4314/ahs.v15i4.34
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reaction reporting among health care workers at Mulago National Referral and Teaching hospital in Uganda

Abstract: Background: Adverse Drug Reactions (ADRs) are an important contributor to patient morbidity and hospitalisation in Uganda. Under-reporting of ADRs may increase medicine-induced morbidity and mortality among patients. This study determined the extent of ADR reporting, and associated factors, among healthcare workers in Uganda. Methods: A quantitative, cross-sectional, study was conducted. Pretested, semi-structured questionnaires were administered to 289 randomly sampled healthcare workers over a three-month pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 17 publications
(40 reference statements)
7
31
2
Order By: Relevance
“…The qualitative result also indicated that shortage of thereportingform in hospitals was contributed to under reporting of the ADR cases. This was in line with studies conducted inEthiopia and South India [19,44].Study conducted in Uganda was also indicated the availability of ADR reporting is essential for ADR reporting [43] and the unavailability of the ADR reporting format is the common discouraging factor for ADR reporting [45].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The qualitative result also indicated that shortage of thereportingform in hospitals was contributed to under reporting of the ADR cases. This was in line with studies conducted inEthiopia and South India [19,44].Study conducted in Uganda was also indicated the availability of ADR reporting is essential for ADR reporting [43] and the unavailability of the ADR reporting format is the common discouraging factor for ADR reporting [45].…”
Section: Discussionsupporting
confidence: 84%
“…In addition, experienceddoctors had the probability of attending in-service trainings and different scientific conferences. Study also revealed that years of experience doctors and others health workers were associated with knowledge and attitude towards PV and ADR reporting [42,43]. Doctors who claimed ADR reporting form exist in their hospital werealmostfour times more likely to report ADR cases as compared to those doctors who claimed that it didn't exist in their hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Data was collected using structured self-administered questionnaire with information on socio-demographic characteristics, knowledge, attitude and practice on ADRs reporting adapted from reviewing different literatures and previous studies 11, [14][15][16][17][18] .…”
Section: Data Collection Instrument and Interpretation Of Resultsmentioning
confidence: 99%
“…Adverse drug reactions (ADRs) are a major public health problem that causes increased mortality, morbidity and costs, including increased hospital admissions and length of stay [1][2][3][4][5][6][7][8][9]. Physicians, pharmacists, dentists and nurses are in a position to play a key role in pharmacovigilance programmes; however, under-reporting of ADRs is common across countries especially in low-and middle-income countries (LMICs) [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%